2013
DOI: 10.1061/(asce)mt.1943-5533.0000596
|View full text |Cite
|
Sign up to set email alerts
|

High-Volume Fly Ash Concrete with and without Hydrated Lime: Chloride Diffusion Coefficient from Accelerated Test

Abstract: Fly ash changes the microstructure of paste and can increase concrete durability. Calcium hydrated lime was added to concrete with 50% of the cement, by weight, substituted with fly ash, with the intent of replacing some of the calcium hydroxide consumed by the pozzolanic activity. Three proportions of mixes were studied: concrete with high early strength cement (HESC), concrete with 50% HESC and 50% fly ash, and concrete with 50% HESC, 50% fly ash and an additional 20% of hydrated lime. They were then tested … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 20 publications
(25 reference statements)
0
20
0
1
Order By: Relevance
“…This will also enable us to estimate diffusivity from a small concrete sample or even concrete pieces, which is not possible in diffusivity test. Furthermore, in the penetration test of chloride ion, the effect of heat generated by electrical potential difference was concerned [6], and this effect was verified by estimating the diffusivity from pore structure to validate the accuracy of the experiment.…”
mentioning
confidence: 94%
“…This will also enable us to estimate diffusivity from a small concrete sample or even concrete pieces, which is not possible in diffusivity test. Furthermore, in the penetration test of chloride ion, the effect of heat generated by electrical potential difference was concerned [6], and this effect was verified by estimating the diffusivity from pore structure to validate the accuracy of the experiment.…”
mentioning
confidence: 94%
“…Moreover, they concluded that use of fly ash changed density and amount of calcium hydroxide in concrete were reduced. [18] Homnuttiwong (2012) investigated compressive strength, water permeability and abrasion resistance of high volume fine fly ash and fine ground palm oil fuel ash concrete. They replaced up to 70% Portland cement type I by fine fly ash (FFA) and fine ground palm oil fuel ash (GPA).…”
Section: International Journal For Research In Applied Science and Engimentioning
confidence: 99%
“…Hoppe Filho [7] showed that fly ash tends to reduce the alkalinity of the concrete due to calcium hydroxide consumption, which is the main controlling factor of pH in cement pastes. (g) Hoppe Filho et al [8] investigated the use of high contents of fly ash in the concrete mix proportion and also showed great decrease of the chloride diffusion coefficient in concretes with fly ash in their composition. (h) Heede and Belie [9] studied concretes with 15% of the Portland cement replaced by fly ash, using accelerated carbonation test and reinforcement depassivation time.…”
Section: Introductionmentioning
confidence: 99%